Telomere organization and the interstitial telomeric sites involvement in insects and vertebrates chromosome evolution - Vicari, Marcelo Ricardo; Bruschi, Daniel Pacheco; Cabral-De-mello, Diogo Cavalcanti [UNESP]; Nogaroto, Viviane (FapUNIFESP (SciELO), 2022)
Telomere has a central role in chromosomal stability events. Chromosome ends organized in telomere-loop prevent activation of DNA damage response (DDR) mechanisms, thus keeping the chromosome structure organized. On the other hand, free chromosome ends, dysfunctional telomeres, and interstitial telomeric sequences (ITS) can trigger chromosome rearrangements. Here, the telomere organization, function, and maintenance mechanisms, in addition to ITS types and their involvement in chromosome changes, were revisited. Despite a general (TTAGGG)n sequence being present in vertebrate telomeres, insects show more diversification of their telomere motif. The relation between ITS and chromosome rearrangements was observed in insects and vertebrates, demonstrating different types of genome organization and distribution. Some ITS cannot be considered relicts of chromosome rearrangements because probable they were inserted during a double-strand break repair mechanism. On the other hand, the involvement of telomere sequences participating or triggering chromosome rearrangements or organizing satellite DNA components in several species groups is evident. The genomic assembling advances and applying other methodologies over ITS, and their flanking regions, can help to understand the telomere participation in the chromosomal evolution in species groups with highly diversified karyotypes.
Keywords: Chromosome rearrangements; fluorescence in situ hybridization; heterochromatin; ITS; karyotype evolution